Public policitymaking - Anderson, James E. (New York: Houghton Mifflin Co., 2000)
Contents : The estudy of public policy, the policy -Makers and their enviroment,policy formation , problems, agendas, and formulation,policy adoption,budgeting and public policy,policy implementation,policy impact,evaluation and change
Keywords: Ciencias Políticas; Planeamiento